2021
DOI: 10.1002/agj2.20625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced nitrogen application rate on drip‐irrigated cotton dry matter accumulation and yield under different phosphorus and potassium managements

Abstract: To elucidate effects of reduced N application rate on dry matter accumulation and yield of drip-irrigated cotton (Gossypium hirsutum L.) under different phosphorus and potassium managements (PK-Ms), field studies with four reduced N application rates and four PK-Ms were conducted in 2018 and 2019. Results show that after early peak boll-forming (PB) stage, the leaf area (LA) in N3PK-M3 was the highest among all treatments. The net assimilation rate (NAR), crop growth rate (CGR), boll dry weight (BDW), and boll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Three cotton plants were selected from each plot at the full square stage (FS), the full flowering stage (FF), the early-full bolling stage (EFB), the late-full bolling stage (LFB), and the boll-opening stage (BO), and divided into leaves, stems and reproductive organs. Afterward, the different parts were placed at 105 • C for 30 min and then dried at 80 • C until their weights were constant [5,10]. The Nc, Pc, and Kc in cotton leaves, stems, and reproductive organs were estimated, as well as the N accumulation (Na), P accumulation (Pa), and K accumulation (Ka) in cotton plants.…”
Section: Sample Collection and Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cotton plants were selected from each plot at the full square stage (FS), the full flowering stage (FF), the early-full bolling stage (EFB), the late-full bolling stage (LFB), and the boll-opening stage (BO), and divided into leaves, stems and reproductive organs. Afterward, the different parts were placed at 105 • C for 30 min and then dried at 80 • C until their weights were constant [5,10]. The Nc, Pc, and Kc in cotton leaves, stems, and reproductive organs were estimated, as well as the N accumulation (Na), P accumulation (Pa), and K accumulation (Ka) in cotton plants.…”
Section: Sample Collection and Determinationmentioning
confidence: 99%
“…Rational fertilization management can reduce production costs without reducing yields [5,10], but the variation in N, P, and K content of cotton at different yield levels during critical growth stages remains to be studied. Research has demonstrated that N, P, and K contents and accumulation could provide a reliable evaluation of the crop growth conditions and yield predictions [11,12].…”
Section: Introductionmentioning
confidence: 99%